The geothermal potential in Spain. (April 2016) - Colmenar-Santos, Antonio; Folch-Calvo, Martin; Rosales-Asensio, Enrique; Borge-Diez, David
Abstract: With a potential geothermal generation of 610 GWt, Spain constitutes a promising EU-28 country for geothermal direct heating systems and binary cycle electricity production. Spain has a need to reduce energy consumption in buildings and in the secondary sector in order to comply with the Spanish Energy Plan 2011–2020, which establishes an objective of 50 MWe of electricity generation from geothermal energy and 66 MWt for direct heating use. Geothermal pumps are admissible in low and medium temperature heating schemes, but to achieve these energy savings targets, the most interesting way to generate energy is by using a CHP production from binary cycle plants. An analysis determining the energy consumption for Spanish dwellings shows that with a low-temperature design concept for district heating distribution, an organic Rankine cycle plant of 15 MWt with a geothermal temperature supply of 105 °C and a vector transportation fluid mass of 100 kg/s can cover 3% of the expected targets of electricity from geothermal sources and 15% of that expected for direct heating.